Follistatin-Like 3 Enhances Invasion and Metastasis via β-Catenin-Mediated EMT and Aerobic Glycolysis in Colorectal Cancer - Li, Yuqiang; Tian, Mengxiang; Liu, Wenxue; Wang, Dan; Zhou, Zhongyi; Pei, Qian; Huang, Yan; Tan, Fengbo; Güngör, Cenap (Frontiers in Cell and Developmental Biology, 2021)
Previous studies reported that Follistatin-like 3 (FSTL3) is abundantly expressed in several solid tumors and participate in the regulation of cell metabolism. However, the clinico-pathological significance, biological role and molecular mechanism of FSTL3 in colorectal cancer (CRC) is still unclear. Here we report that the expression level of FSTL3 in colon cancer specimens was significantly higher, compared to normal tissue and interestingly, the expression of FSTL3 was related to lymph node metastasis, tumor stage, tumor size, and intravascular emboli (IVE). As an upstream molecular event, we found that transcriptional regulation of FSTL3 was highly dependent on YAP1 de-phosphorylation events and that increased FSTL3 expression readily activated the β-Catenin pathway, which is a well-known signaling hub that promotes EMT processes and aerobic glycolysis in cancer cells. We found that elevated FSTL3 expression strongly promotes migration, invasion and metastatic formation of CRC cells by directly activating β-Catenin -mediated EMT and aerobic glycolysis. In the xenograft mouse model, FSTL3 expression was linked to increased metastatic formation of CRC cells. Together, the activation of YAP1 induces FSTL3 expression. FSTL3-mediated β-Catenin pathway activation promotes EMT and aerobic glycolysis and therefore affecting the invasive and metastatic capacity of CRC cells. The abundant FSTL3 expression is a poor prognostic factor and pharmacological targeting of YAP1 can counteract FSTL3 expression, suggesting a promising therapeutic target for anti-metastatic strategies in patients suffering from CRC.